2D experiments and numerical simulation of the oscillatory shallow flow in an open channel lateral cavity. (February 2021) - Navas-Montilla, A.; Martínez-Aranda, S.; Lozano, A.; García-Palacín, I.; García-Navarro, P.
Highlights: High resolution 2D space-time data of water surface and velocity oscillation are provided. Seiche amplitude maps are presented for different oscillation modes. A virtually 1D longitudinal seiche is observed for high Froude numbers ( F r = 0.8 ). The experiments are well reproduced using a 2D third order shallow water model. The experimental dataset can serve as a benchmark for other numerical models. Abstract: Steady shallow flows past an open channel lateral cavity can induce the excitation of an eigenmode of a gravity standing wave inside the cavity, called seiche, which may be coupled with the shedding of vortices at the opening of the cavity. The presence of the seiche is of fundamental interest as it enhances the mass exchange between the main channel and the cavity. Measurements of the time evolution of the water surface are not often found in the literature for this type of flows. In this work, an experimental and numerical study of a shallow flow past a channel lateral cavity is carried out. The main novelty is the use of a pioneering non-intrusive experimental technique to measure the water surface at the channel-cavity region. This optical technique offers high resolution 2D data in time and space of the water surface evolution, allowing to determine the relevant features of the seiche oscillation. Such data are supplemented with Particle Image Velocimetry measurements. Furthermore, the experiments are numerically reproduced using a high-resolution depth-averaged URANS shallow water model, under the assumption that shallow water turbulence is mainly horizontal. The experimental and numerical results are analyzed in the frequency domain. High-resolution two-dimensional amplitude oscillation maps of the seiche phenomenon, as well as velocity fields, are presented. The high quality of the experimental data reported in this work makes this data set a suitable benchmark for numerical simulation models in order to evaluate their performance in the resolution of turbulent resonant shallow flows.